Infor-Mash. (Liège : Mouvement d'Action et de Solidarité des Homophiles, 1972)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : 32 Quai de l'Ourthe, 4000 Liège ; vanaf (1975) sep. : 24 rue A. Stouls, 4020 Liège
Frans
Periodiek